Studi Penghematan Air pada Sistem Plambing Air Bersih di Apartemen Menara Cibinong Tower Mahoni - Fuad Muhamad; Eka Wardhani (Fakultas Teknik, 2021)
The Cibinong Tower Mahoni Tower Apartment located in Bogor Regency is a residential residence consisting of 21 floors. Apartment development is influenced by the need for housing which continues to increase along with the rate of population growth and limited land. The impact of apartment construction will affect the availability of clean water in the future due to an increase in the need for clean water. West Java Provincial Regulation Number 13 of 2013 concerning Buildings requires developers to carry out water efficiency. Referring to the regulation, this apartment implements water conservation based on the Green Building Council Indonesia (GBCI) concept which aims to save water use. The research method used is the use of water-saving plumbing features which aims to find out how efficient the use of water is. Based on the results of the study, the population in the Cibinong Tower Mahoni Tower Apartment was 794 people with clean water needs of 67,366.68 l/day. The use of water-saving plumbing equipment can save water use by 6.01% or 4,060.71 l/day.